2020
DOI: 10.3390/polym13010035
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium, Morphology, and Physico-Mechanics in Epoxy–Thermoplastic Mixtures with Upper and Lower Critical Solution Temperatures

Abstract: The mutual solubility of epoxy oligomer with polysulfone (PSU) and polyethersulfone (PES) was studied by optical interferometry. Additionally, phase diagrams (PDs) were plotted and their evolution during the curing process was shown. The phase structures of modified hardened systems, as well as their tensile strengths, elastic moduli, and crack resistance, have been studied by scanning electron microscopy and physico-mechanical techniques. The effect of initial components’ mutual solubility on the phase struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Previously, in [ 42 ], it was shown that the PSU–EO system is completely compatible over the full concentration temperature range from 25 to 270 °C. Figure 1 shows typical interferograms characterizing the solubility of the components of the PSU–FGE and EO–FGE systems at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, in [ 42 ], it was shown that the PSU–EO system is completely compatible over the full concentration temperature range from 25 to 270 °C. Figure 1 shows typical interferograms characterizing the solubility of the components of the PSU–FGE and EO–FGE systems at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a homogeneous mixture is formed upon mutual dissolution of the components of ternary systems at 100 °C. Further addition of a curing agent to the system and temperature activation of the process of forming a three-dimensional spatial network of chemical bonds will lead to an increase in viscosity, a decrease in thermodynamic compatibility, and, as a result, the formation of phase structures [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…SEM images in Figure 2a showed that the fibers of the pristine PU membranes melted after autoclave sterilization, while the structure of PU/PES-4/6 and 2/8 membranes remained intact, which was due to the excellent temperature performance of the PES molecular chain. 34,35 Simultaneously, changes in the pore size after sterilization were investigated to further highlight the autoclavable performance of the PU/PES membrane. It was clearly shown that there were no significant changes in the pore size of PU/PES-4/6 and 2/8 membranes after the autoclave sterilization (Figure 2g), indicating its remarkable structure stability against high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the compatibility of components in the entire concentration range, we used the method of optical interferometry. All of the measurements were performed on an ODA–2 diffusiometer (IPCE RAS, Moscow, Russia) [ 13 , 45 , 46 ]. A helium–neon laser (λ = 632.8 nm) was used as a source of monochromatic light with a parallel beam.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the development of modern fibrous polymer composite materials, it is important to have finishing compositions that not only ensure the good wetting effect of the surface of the fiber but also provide the affinity at the treated fiber–binder interface. Recently, along with thermoset binders, various thermoplastic, thermoset matrices modified by thermoplastics [ 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and fibrous composite materials [ 4 , 5 , 6 , 19 , 20 , 21 , 22 ] have been widely used. Thus, the problem of the modification of the existing finishing materials with the aim of directly changing the surface energy characteristics is urgent.…”
Section: Introductionmentioning
confidence: 99%